Laterality in sports : theories and applications - Loffing, Florian; Hagemann, Norbert, 1971-; Strauss, Bernd, 1959-; MacMahon, Clare (London, United Kingdom : Academic Press is an imprint of Elsevier, 2016)
Laterality in Sports: Theories and Applications summarizes recent research on the neurophysiological foundations of handedness, and how left or right lateralization (affecting primary hand use, foot use, and eye use) affects motor control, performance outcome, skill acquisition, and achievement of sports expertise-both for one-on-one sports and team sports. As laterality research has matured, greater focus has been given to applications in human endeavors and, in particular, sport. The book examines performance within individual sports, and discusses the coaching ramifications of coaching to a specific lateralization preference.
The Effects of Hybrid Control on Motor Performance and AdaptationHemispheric Specializations for Control of Limb Dynamics and Limb Impedance; Motor Asymmetries in Left-Handers; Application to Sports and Athletics; Summary and Conclusions; Chapter 9. Effector Transfer; The Structure, Control, and Effector Transfer of Movement Sequences; Effector Transfer Can Disrupt Sequence Concatenation; Multiple Representations; Implicit Versus Explicit Coding; Handedness, Hemispheric Asymmetries, and Effector Transfer; Summary.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed September 1, 2016).
Includes bibliographical references and index.
Keywords: Laterality; Sports -- Psychological aspects; Sports -- Physiological aspects; PSYCHOLOGY -- Physiological Psychology; Laterality; Sports -- Physiological aspects; Sports -- Psychological aspects; Bewegungssteuerung; Sport; Kognitionswissenschaft; Neuropsychologie; Sportliche Leistung; 2; Functional Laterality; Electronic books; Electronic book; Aufsatzsammlung